2007
DOI: 10.1590/s0100-879x2007000300011
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind comparison of the effect of the antipsychotics haloperidol and olanzapine on sleep in mania

Abstract: The effects of haloperidol and olanzapine on polysomnographic measures made in bipolar patients during manic episodes were compared. Twelve DSM-IV mania patients were randomly assigned to receive either haloperidol (mean ± SD final dosage: 5.8 ± 3.8 mg) or olanzapine (mean ± SD final dosage: 13.6 ± 6.9 mg) in a 6-week, double-blind, randomized, controlled clinical trial. One-night polysomnographic evaluation was performed before and after the haloperidol or olanzapine treatment. Psychopathology and illness sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These were carried out in those with schizophrenia and those with mood disorders and indicate that this medication decreases sleep onset latency and wake time after sleep onset and increases sleep efficiency, sleep quality ratings and the amount and percentage of slow-wave sleep. 178185 Small studies also document that cloazapine decreases awakenings, and wake time after sleep onset and increases total sleep time and amount of slow-wave sleep 186187 and that risperidone 0.5–1 mg decreases wake time after sleep onset as well as the amount of REM sleep. 188 …”
Section: The Sleep Effects Of Psychiatric Treatments;mentioning
confidence: 99%
“…These were carried out in those with schizophrenia and those with mood disorders and indicate that this medication decreases sleep onset latency and wake time after sleep onset and increases sleep efficiency, sleep quality ratings and the amount and percentage of slow-wave sleep. 178185 Small studies also document that cloazapine decreases awakenings, and wake time after sleep onset and increases total sleep time and amount of slow-wave sleep 186187 and that risperidone 0.5–1 mg decreases wake time after sleep onset as well as the amount of REM sleep. 188 …”
Section: The Sleep Effects Of Psychiatric Treatments;mentioning
confidence: 99%
“…In both case 2 and 3, olanzapine was prescribed off-label at bedtime to help promote sleep. In a small double-blind, randomized, placebo-controlled trial, olanzapine has been shown to improve sleep efficiency, total sleep time, and sleep latency in patients with depression and bipolar disorder (27), superior to haloperidol in bipolar patients during manic episodes (28), and more effective than risperidone for the treatment of paradoxical insomnia (29).…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic medications are of particular interest due to their use in the management of delirium and have been observed to have variable effects on sleep architecture. Haloperidol has been shown to increase sleep efficiency, whereas the atypical agents, olanzapine and risperidone, have the additional effect of promoting slow wave sleep[ 99 , 109 - 111 ].…”
Section: Causes Of Sleep Disturbance In the Critically Illmentioning
confidence: 99%